Methods for analysis in pharmacogenomics: lessons from the Pharmacogenetics Research Network Analysis Group. (February 2009) - Srinivasan, Balaji S; Chen, Jinbo; Cheng, Cheng; Conti, David; Duan, Shiwei; Fridley, Brooke L; Gu, Xiangjun; Haines, Jonathan L; Jorgenson, Eric; Kraja, Aldi; Lasky-Su, Jessica; Li, Lang; et al.
Each year, the Pharmacogenetics Research Network (PGRN) holds an analysis workshop for the members of the PGRN to share new methodologies, study design approaches and to discuss real data applications. This event is closed to members of the PGRN, but the methods presented are relevant to others conducting pharmacogenomics research. This special report describes many of the novel approaches discussed at the workshop and provides a resource for investigators in the field performing pharmacogenomics data analysis. While the focus is pharmacogenomics, the methods discussed are far ranging and have relevance to all types of genetic association studies: identifying noncoding variants and tag-SNPs, haplotype analysis, multivariate techniques, quantitative trait analysis, gene––gene and gene––environment interactions, and genome-wide association studies. The goal is to introduce readers to the topics discussed at the workshop and provide a direction for future development of analysis tools and methods for analysis of pharmacogenomic data.